Occurrence of Escherichia species in vended red meat in Khartoum State, Sudan - Ahmed, Ala Kheder Albadawe Mohamed; Al Sanosi, Sulieman Mohamed (Journal of Veterinary Medicine and Animal Production, 2021)
The aim of this study was to determine the incidence of Escherichia species in raw red meat in Khartoum State, Sudan. A total of 75 random samples of raw meat, were collected from different localities in three towns (Khartoum, Omdurman and Khartoum North), Khartoum state, Sudan. These samples were subjected to bacteriological analysis using MacConkey meduim and tentative identification by biochemical tests. The incidence of Escherichia spp was 36%. Four types of Escherichia species were isolated; E. coli (20%), E. vulneris (6.6%) followed by E. albertii (5.3%) and E fergusonii (4%).Considering the fact that Escherichia species contribute to the burden of food borne illness, more hygienic measures should be applied to improve the quality of the meat to ensure maximum safety to consumers.